IDENTIFIKASI GAYA BELAJAR MURID PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS TINGGI SDN 15 KOTO BARU : PENDEKATAN DESKRIPTIF KUANTITATIF MODEL VAK - Resha Albadri; Wiwik Okta Sulisawati; Martiya Nurni Khairita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The suboptimal teaching and learning process due to the lack of specific identification of students' learning preferences in internalizing civics material is the background of this research. These operational problems trigger a mismatch between teachers' instructional strategies and children's cognitive characteristics, which risks reducing the motivation and academic resilience of upper-grade students. The main focus of this scientific study is to analyze the learning profile tendencies using the visual, auditory, kinesthetic (VAK) model in the Pancasila Education subject. The steps of this descriptive quantitative approach are operated through the distribution of a 14-statement questionnaire filled out by a total sample of 41 fourth, fifth, and sixth-grade students at SDN 15 Koto Baru using a total sampling technique. The actual data processing procedure is executed in a structured manner using descriptive percentage statistics techniques. Quantitative data empirically reveals the dominance of the visual style with an average of 61.67 percent, spread over scores of 55 percent in fourth grade, 70 percent in fifth grade, and 60 percent in sixth grade. Auditory preferences recorded an average of 44.67 percent, while the kinesthetic type decreased with increasing grade levels with an average of 35.00 percent. The main conclusion confirms a shift in learning modalities influenced by students' levels of cognitive maturity and verbal literacy. Educators are recommended to consistently design differentiated module drafts. ABSTRAK Ketidakoptimalan proses belajar-mengajar akibat belum teridentifikasinya preferensi belajar siswa secara spesifik dalam internalisasi materi kewarganegaraan melatarbelakangi penelitian ini. Masalah operasional tersebut memicu ketidaksesuaian strategi instruksional guru dengan karakteristik kognitif anak yang berisiko menurunkan motivasi serta ketahanan akademik siswa kelas tinggi. Fokus utama kajian ilmiah ini adalah menganalisis kecenderungan profil belajar menggunakan model visual, auditory, kinesthetic (VAK) pada mata pelajaran Pendidikan Pancasila. Langkah-langkah pendekatan kuantitatif deskriptif ini dioperasikan melalui penyebaran kuesioner angket 14 pernyataan yang diisi oleh sampel total sejumlah 41 murid kelas empat, lima, dan enam di SDN 15 Koto Baru melalui teknik total sampling. Prosedur pengolahan data aktual dieksekusi secara terstruktur memakai teknik statistik deskriptif persentase. Data kuantitatif secara empiris menyingkap dominasi gaya visual dengan rata-rata 61,67 persen, yang tersebar atas skor 55 persen di kelas empat, 70 persen di kelas lima, dan 60 persen di kelas enam. Preferensi auditori mencatat rata-rata 44,67 persen, sedangkan tipe kinestetik mengalami penurunan seiring kenaikan jenjang kelas dengan rata-rata 35,00 persen. Simpulan utama menegaskan adanya pergeseran modalitas belajar yang dipengaruhi oleh tingkat kematangan kognitif serta literasi verbal siswa. Pendidik direkomendasikan merancang draf modul berdiferensiasi secara konsisten.